Multidisciplinary care results in similar maternal and perinatal mortality rates for women with and without SCD in a low‐resource setting. Issue 2 (5th December 2018) - Oppong, Samuel A.; Asare, Eugenia V.; Olayemi, Edeghonghon; Boafor, Theodore; Dei‐Adomakoh, Yvonne; Swarry‐Deen, Alim; Mensah, Enoch; Osei‐Bonsu, Yvonne; Crabbe, Selina; Musah, Latif; Hayfron‐Benjamin, Charles; Covert, Brittany; et al.
Abstract : In Africa, the maternal mortality rate in sickle cell disease (SCD) is ~10%. Our team previously demonstrated an 89% decrease in mortality rate in a before‐and‐after feasibility study among women with SCD living in low‐resource setting in Ghana. In the same cohort including additional participants with and without SCD, we used a prospective cohort design to test the hypothesis that implementing a multidisciplinary care team for pregnant women with SCD in low‐resource setting will result in similar maternal and perinatal mortality rates compared to women without SCD. We prospectively enrolled pregnant women with and without SCD or trait and followed them up for 6‐week postpartum. We tested the newborns of mothers with SCD for SCD. We recruited age and parity matched pregnant women without SCD or trait as the comparison group. Maternal and perinatal mortality rates were the primary outcomes. A total of 149 pregnant women with SCD (HbSS, 54; HbSC, 95) and 117 pregnant women without SCD or trait were included in the analysis. Post‐intervention, maternal mortality rates were 1.3% and 0.9% in women with and without SCD, respectively (P = 1.00); the perinatal mortality rates were 7.4% and 3.4% for women with and without SCD, respectively ( P  = 0.164). Among the mothers with SCD, ~15% of newborns had SCD. Multidisciplinary care of pregnant women with SCD may reduce maternal and perinatal mortality rates to similar levels in pregnant women without SCD in low‐resource settings. Newborns of mothers with SCD have a high rate of SCD.